Collections of Geophyte in Harran University Herbarium (HARRAN) - Nour Alhasan; Hasan Akan (Turkish Journal of Bioscience and Collections)
This study was carried out to re-evaluate the geophyte samples found in the Herbarium of Harran University (HARRAN) between 2018 and 2020. 850 plant samples belonging to geophytes found in Harran Herbarium were examined. Plant samples consisting of 11 families and 146 taxa belonging to 33 genera were identified. The families with the most taxa among the identified samples are Amaryllidaceae (32), Asparagaceae (30), Liliaceae (18), Iridaceae (24), Orchidaceae (8) and Araceae (8). The richest species in terms of taxa number are: Allium L. (28), Ornithogalum L. (13), Gagea Salisb. (8), Iris L. (11) and Bellevalia Lapeyr. (5). 19 of these taxa are endemic to Turkey. In the evaluations made in HARRAN herbarium, it was determined that 18 taxa fell into synonyms.